The management of the patient with an acute spinal cord injury - Brown, Doug (Henry Stewart Talks, 2011)
Acute spinal cord injury, Incidence and prevention, Management at accident scene and first hospital, Neurologic examination, Spinal shock, Imaging, Treatment of vertebral column injury, Management of organ secondarily affected by SCI, Prevention of secondary complications